Localisation of an impulsive acoustic source in an urban environment - Hewett, D (2009)
This paper concerns the imerse problem of localising an impulsive acoustic source in an urban environment using measurements from multiple receivers (microphones) distributed through the propagation domain. In free space the im erse problem is readily solved by Time Difference Of Arrival (TDOA) localisation. In urban environments there may not be a line- of-sight (LOS) between the source and each receiver, and an application of the free spaceTDOA method may produce erroneous results, especially if the streets are narrow. In thiswork the case of a network of 2D streets intersecting at right angles is considered, and analternative TDOA method is proposed which explicitly takes into account the non-line-of-sight(NLOS) propagation. The results of a numerical simulation are also presented, together withcomparisons with the free space method. The applicability of the new method to the 3D caseis also discussed.